2018
DOI: 10.4155/fmc-2017-0199
|View full text |Cite
|
Sign up to set email alerts
|

Strategies against Methicillin-Resistant Staphylococcus Aureus Persisters

Abstract: Chronic Staphylococcus aureus infections are complicated by frequent relapses not only from the development of drug resistance to conventional antibiotics, but also through the formation of persister bacterial cells. Bacterial persisters are in a transient, metabolically inactive state, making conventional antibiotics that target essential cellular growth processes ineffective, resulting in high clinical failure rates of antibiotic chemotherapy. The development of new antibiotics against persistent S. aureus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 110 publications
0
34
0
Order By: Relevance
“…A significant challenge in the treatment of IE concerns the ability of colonizing bacteria, primarily Staphylococcus and Streptococcus spp., to adhere to cardiac surfaces and form biofilm-like vegetations which can be refractory to antibiotics and immune surveillance, resulting in persistent and relapsing infections (4)(5)(6). Current IDSA guidelines recommend either vancomycin or daptomycin for the treatment of IE caused by methicillin-resistant Staphylococcus aureus (MRSA) in adults (3,7); however, vancomycin has been associated with poor clinical outcomes (4,8), and daptomycin, the most recent drug approved by the U.S. Food and Drug Administration (in 2006) for S. aureus bloodstream infections (9), exhibited a clinical cure rate of 44.2% in a phase 3 trial for S. aureus bacteremia and endocarditis (10).…”
mentioning
confidence: 99%
“…A significant challenge in the treatment of IE concerns the ability of colonizing bacteria, primarily Staphylococcus and Streptococcus spp., to adhere to cardiac surfaces and form biofilm-like vegetations which can be refractory to antibiotics and immune surveillance, resulting in persistent and relapsing infections (4)(5)(6). Current IDSA guidelines recommend either vancomycin or daptomycin for the treatment of IE caused by methicillin-resistant Staphylococcus aureus (MRSA) in adults (3,7); however, vancomycin has been associated with poor clinical outcomes (4,8), and daptomycin, the most recent drug approved by the U.S. Food and Drug Administration (in 2006) for S. aureus bloodstream infections (9), exhibited a clinical cure rate of 44.2% in a phase 3 trial for S. aureus bacteremia and endocarditis (10).…”
mentioning
confidence: 99%
“…Overall, these trials have demonstrated that the focus of infection within tissues is one of strongest drivers of mortality, clinical failure, and microbiological failure in S. aureus bacteremia. Killing intracellular S. aureus could potentially eliminate both dissemination and seeding of S. aureus tissue reservoirs associated with SOC antibiotic failure (12), improving clearance of S. aureus infections.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with S. aureus remains difficult to treat because of the emergence of methicillin-resistant S. aureus (MRSA), biofilm formation in infections involving prosthetic devices, and toxicities that limit dosing of standard-of-care (SOC) antibiotics, such as nafcillin and vancomycin (5)(6)(7)(8)(9)(10). In addition, multiple lines of evidence suggest that survival of antibiotic-susceptible subpopulations of S. aureus contributes to high rates of mortality, morbidity, and treatment failure (11,12). This survival is likely due to multiple causes, including bacterium-specific factors, such as the reduction or cessation of growth, as observed in infective endocarditis, and survival inside host cells (13)(14)(15).…”
mentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus aureus (MRSA) is a major pathogen that causes a wide spectrum of diseases, ranging from minor skin infections to life-threatening diseases such as fatal necrotizing pneumonia, endocarditis and osteomyelitis [1,2]. Numerous factors contribute to the capacity of S. aureus to be a tenacious pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous factors contribute to the capacity of S. aureus to be a tenacious pathogen. One contributing factor is likely acquisition of antibiotic resistance, which causes patients need prolonged treatment and many experience difficulties as a result of antibiotic-resistance or shift to dormant state that causes a high level of tolerance to most conventional antibiotics [1]. In addition, other factors including responding to various environmental stimuli such as nutrient starvation, stress, biofilm formation, has made this bacteria to a recalcitrant pathogen [3].…”
Section: Introductionmentioning
confidence: 99%